If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8t + 8(2t + -6) = 2 + 14t Reorder the terms: 8t + 8(-6 + 2t) = 2 + 14t 8t + (-6 * 8 + 2t * 8) = 2 + 14t 8t + (-48 + 16t) = 2 + 14t Reorder the terms: -48 + 8t + 16t = 2 + 14t Combine like terms: 8t + 16t = 24t -48 + 24t = 2 + 14t Solving -48 + 24t = 2 + 14t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-14t' to each side of the equation. -48 + 24t + -14t = 2 + 14t + -14t Combine like terms: 24t + -14t = 10t -48 + 10t = 2 + 14t + -14t Combine like terms: 14t + -14t = 0 -48 + 10t = 2 + 0 -48 + 10t = 2 Add '48' to each side of the equation. -48 + 48 + 10t = 2 + 48 Combine like terms: -48 + 48 = 0 0 + 10t = 2 + 48 10t = 2 + 48 Combine like terms: 2 + 48 = 50 10t = 50 Divide each side by '10'. t = 5 Simplifying t = 5
| 160=4n^2 | | 8(3t-4)=4(7t-1) | | 3(-2)-2y=10 | | -6x+4y=1 | | 3xsquared-4x-4= | | 12=6-2y+y | | y=3(-2)-7 | | 7(4)-3(25)=42 | | x^2-5y+6=0 | | 18s-17(-19-13s)= | | k+4=-8-2k | | 30c=17*13.10+2 | | (5x^2+3x+5)+(-7x^2+4x-3)= | | 10x^3-20x^2-2x+4=0 | | 16a^2+25b^2=0 | | X^6-2x^4-16x^2-32=0 | | 15x-3y=-12 | | (7s^3-3s+3)+(s^3-6s+2)= | | y^2-625=0 | | 2x^2+2x+4=4x+4 | | -3.33+1.25= | | -13/-8= | | 6-2y+y=12 | | 4x^2-3=13 | | 1.5x+4.6=3.4x-3 | | 23w-78=76 | | -7/1.8=c | | 2-9b+3= | | 5r-(2r+8)=18 | | 2s-9s+7= | | -12/1.8=c | | 15x-21=219 |